1999
DOI: 10.1016/s0002-9440(10)65230-3
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Expression of Cyclooxygenase-2 in Human Atherosclerotic Lesions

Abstract: Cyclooxygenase-1 (Cox-1) and Cox-2 convert arachidonic acid to prostaglandin H(2), the precursor of other prostaglandins and thromboxanes, eicosanoids important in vascular pathophysiology. However, knowledge of the expression of cyclooxygenases within atherosclerotic lesions is scant. This study tested the hypothesis that human atheroma and nonatherosclerotic arteries express the two Cox isoforms differentially. Cox-1 mRNA and protein localized on endothelial and medial smooth muscle cells of normal arteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
220
0
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(236 citation statements)
references
References 65 publications
6
220
0
10
Order By: Relevance
“…In addition, inflammation plays a key role in the initiation and development of atherosclerosis and augmented expression of COX-2 has been found in human atherosclerotic lesions but not in normal arteries (52). The anti-inflammatory properties of ␥T may be important in preventing cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inflammation plays a key role in the initiation and development of atherosclerosis and augmented expression of COX-2 has been found in human atherosclerotic lesions but not in normal arteries (52). The anti-inflammatory properties of ␥T may be important in preventing cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm that both isoforms of COX are present, functional, and involved in relaxation responses to AA. The expression of COX-2 in normal mesenteric arteries was unexpected, given that this isoform is predominantly expressed in disease states such as inflammation and atherosclerosis (1,6,10,31). However, a previous study (12) has reported that both COX-1 and -2 are constitutively expressed in the rat lung vasculature and that COX-2 plays a predominant role in prostanoid-related regulation of pulmonary vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage proteinase expression contributes to the rupture of atherosclerotic plaques, which leads to thrombosis, myocardial infarction, and stroke. Several studies (67)(68)(69) have demonstrated increased COX-2 expression in atherosclerotic lesions. Moreover, COX-2, prostaglandin E synthase, and MMP activities were elevated on the shoulders of symptomatic plaques (70).…”
Section: Discussionmentioning
confidence: 99%